2020
DOI: 10.1155/2020/4395496
|View full text |Cite
|
Sign up to set email alerts
|

Metal Content of Nutritional and Toxic Value in Different Types of Brazilian Propolis

Abstract: Brazilian raw propolis samples (brown, green, red, and yellow) were investigated to evaluate the content of three elements of nutritional value (Cu, K, and Se) and three toxic metals (As, Cd, and Pb). The propolis samples (n = 19) were obtained from different regions of Brazil and analysed by atomic absorption spectrometry after microwave-assisted digestion. A descriptive analysis of the variables was carried out, and nonparametric tests (Kruskal–Wallis or Mann–Whitney) were performed to verify the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Comparing our results with the elements’ levels measured in Brazilian propolis [ 46 , 47 ] indicated lower levels of both nutritional and toxic elements in samples of propolis collected in Poland. In addition, Polish propolis seems to be less contaminated than samples collected in Spain [ 48 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Comparing our results with the elements’ levels measured in Brazilian propolis [ 46 , 47 ] indicated lower levels of both nutritional and toxic elements in samples of propolis collected in Poland. In addition, Polish propolis seems to be less contaminated than samples collected in Spain [ 48 ].…”
Section: Discussionsupporting
confidence: 74%
“…Levels of 24 chemical elements were determined in all samples of bee products. We measured one of the broadest spectra of chemical elements (including micro- and macronutrients, heavy metals, and trace elements) in bee products compared to the available literature [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In this study, we examined various beehive matrices (bee pollen, propolis, and royal jelly) collected over two years from the same area.…”
Section: Resultsmentioning
confidence: 99%
“…Propolis is an apicultural product obtained mainly from Apis mellifera bees that has compounds such as wax, resins, and minor constituents, including pollen and minerals [1]. One cannot fail to mention the contaminants commonly found in propolis, such as toxic metals and herbicides [14,15], among others. Salatino and Salatino [16] point out that the composition of propolis declared in many scientific articles for many years (resins and vegetable balsam 50%, bee wax 30%, pollen 5%, and essential and aromatic oils 10%) are generic (without details of the methodologies used to determine these parameters), considering that the composition varies mainly with the geographic location and ecosystem.…”
Section: Propolis Compositionmentioning
confidence: 99%
“…Dereplication studies using HPLC-DAD-ESI-MS/MS identified the presence of pyrrolizidine alkaloids 7-(3-methoxy-2-methylbutyryl)-9-echimidinylretronecine and caffeoylquinic acid-O-arabinoside [42], but studies that report the isolation and identification of alkaloids from propolis using MS and NMR are rare. Trace elements such as Al, Ca, Fe, K, Mg, P, Zn, Cr, Ni, and Cu and possible toxic metals (As, Cd, and Pb) have also been reported [43][44][45].…”
Section: Other Constituentsmentioning
confidence: 99%